A 60 Year Old Man with Severe Corneal Ulcer of The Left Eye: A Case Report - Zufara, Iffa Maulida; Ariany, Dessira Rizka Tri (Yayasan Ahmad Mansyur Nasirah, 2025)
Corneal ulcer is an ophthalmological emergency characterized by corneal epithelial defects with stromal involvement, which can be caused by both infective and non-infective etiologies. This condition can lead to severe complications such as corneal scarring, perforation, endophthalmitis, and even permanent blindness if not treated promptly. The purpose of this study was to identify and manage a 60-year-old man with a severe corneal ulcer in the left eye. This study used a case report method that describes a patient with a clinical diagnosis of corneal ulcer based on anamnesis findings, physical examination, supporting examinations, and the treatment given. The results showed that the management that can be done is by administering rapid and appropriate therapy according to the culture and results of the sensitivity test of the causative microorganism. Prognosis depends on the severity and speed of therapy administration, the type of causative microorganism, and the presence or absence of complications that arise. Case report of a 60-year-old man came with complaints of left eye pain for 20 days, accompanied by redness, photophobia, epiphora, and blurred vision. The initial history was irritation after exposure to